Netupitant/palonosetron (NEPA; Akynzeo®) combination in prevention of the nausea and vomiting in patients with breast cancer receiving anthracyclinbased chemotherapy - A. G. Kedrova; A. I. Berishvili (ABV-press, 2023)
Chemotherapy-induced nausea and vomiting is a common problem during cancer treatment, especially in breast cancer patients with anthracycline/cyclophosphamide (ас) chemotherapy. Netupitant/palonosetron (NEPA; Akynzeo®) is a fixed-dose combination of two drugs (netupitant, a neurokinin 1 receptor antagonist; and palonosetron, a serotonin 3 receptor antagonist) which target two diferent signalling pathways involved in the induction of vomiting. Approved for use in the prevention of acute and delayed chemotherapy-induced nausea and vomiting in adults, netupitant/palonosetron is given orally or via intravenous infusion as a single dose prior to chemotherapy. In clinical trials, high proportions of patients who received netupitant/palonosetron (used in combination with the corticosteroid dexamethasone) prior to chemotherapy reported no vomiting, no requirement for rescue medication, and no signifcant nausea in the 5 days post chemotherapy. Both the oral and intravenous formulations of the drug combination are well tolerated. Thus, netupitant/palonosetron is a simple, convenient and efective drug combination for the prevention of acute and delayed xhemotherapy-induced nausea and vomiting in patients receiving chemotherapy that has a moderate to high emetogenic potential.